Pengaruh Ekstrak Kulit Pisang Kepok (Musa Paradisiaca L.) Sebagai Antidepresan Pada Mencit (Mus Musculus) Dengan Acute Restraint Stress - Dhea Safitri Ramadhani; Maftuchah Rochmanti; Erika Vitri Yulianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: Banana peel is an organic waste which is known to have various benefits, especially as an antidepressant for mental health. It inspired to conduct a research on various type of banana peels in Indonesia, particularly on Kepok banana which has been widely studied. This research aimed to prove the effect of Kepok banana peel extract (Musa paradisiaca L.) as an antidepressant in mice (Mus musculus) with acute restraint stress.Method: This research used a laboratory experimental design. The male mice were acclimatized for 3 days. Twenty-four mice were then divided evenly into 4 groups. The first group was given banana peel extract (Musa paradisiaca L.) at a dose of 200 mg / kgBW, the second group was given a dose of 400 mg / kgBB, the third group was given a dose of 800 mg / kgBW and the fourth group was given water as control. Each group was given a dose orally for 14 days and ARS depressed induction for 7 hours. Subsequently, mice were treated to assess depression behavior using the tail suspension test (TST) and forced-swim test (FST) to determine the duration of immobility.Result: The result showed that there was a significant difference (p<0.01) between the control group and the experimental group, at TST there was a significant difference (p<0.01) between two doses of 400 mg / kgBW and 800 mg / kgBW, as well as on the forced-swim test (FST). In addition, there was a significant difference (p<0.01) between two doses of 200 mg / kgBW and 800 mg / kgBW, and between two doses of 400 mg / kgBW and 800 mg / kgBW. Conclusion: These result confirmed that Kepok banana peel extract (Musa paradisiaca L.) was an effective antidepressant in reducing immobility duration with acute restraint stress.